MINAT MEMBACA DAN MENULIS AL-QUR’AN PESERTA DIDIK SDN 3 TUMBANG JUTUH KECAMATAN RUNGAN KABUPATEN GUNUNG MAS - Noormansyah Noormansyah (ADIBA : JOURNAL OF EDUCATION, 2023)
Interest in reading and writing the Qur'an among some school-age children (age 6-12 years) is decreasing because children at that age are still playing, they are also still easily influenced by the social environment of their friends. With their fun playing they forget their obligations as students. This also has an impact on their laziness to study the Koran, especially in reading and writing the Koran. They will look for a lot of reasons when asked to read and write the Koran. This study aims to find out what are the factors causing the decline in reading and writing the Qur'an in school-age children (age 6-12 years) and then help provide solutions in overcoming interest in reading and writing the Qur'an for school-age children in SDN 3 Tumbang Jutuh, Rungan District, Gunung Mas Regency. The research was carried out through a qualitative approach by conducting research at SDN 3 Tumbang Jutuh, Rungan District, Gunung Mas Regency. The data were obtained by means of in-depth interviews, participant observation and documentation. Data analysis was carried out through data reduction (data reduction), data presentation (data display), and drawing conclusions (verification).